If we are not indexed, we do not exist? - Hinzpeter Jaime (International Physiology Journal, 2018)
An opinion editorial comments on indexing and visibility in scholarly communication. It encourages quality, openness, and ethical practices as pathways to discoverability and impact, with concrete steps for journals and authors.